2019
DOI: 10.1186/s13071-019-3406-y
|View full text |Cite
|
Sign up to set email alerts
|

Dirofilaria repens in dogs and humans in Lithuania

Abstract: Background In Lithuania, the first case of canine subcutaneous dirofilariosis was recorded in 2010. Since then, an increasing number of cases of canine dirofilariosis have been documented in different veterinary clinics throughout the country. Human dirofilariosis was diagnosed in Lithuania for the first time in September 2011. However, to the authors’ knowledge, there are no published data on the presence and prevalence of autochthonous dirofilariosis in dogs and humans in the country. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 60 publications
(73 reference statements)
7
26
0
Order By: Relevance
“…In addition, the occult heartworm cannot be confirmed by serological tests when presented as a co-infection with another filarial infection that cross-reacts with the test, especially if associated with D. repens infection (Fig. 2), this type of case resulting from an unknown mechanism of D. repens microfilariae, which shows a suppressive effect on those of D. immitis [38]. The ESDA does not recommend the routine heat-pretreatment of sera in area endemic for these parasitosis, as the only recommends it to resolve the discrepancy between the other tests, particularly when the dog is positive on the microfilaria test and negative by serology, and to confirm a suspicion of clinical disease suggestive of microfilaremia [11, 12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the occult heartworm cannot be confirmed by serological tests when presented as a co-infection with another filarial infection that cross-reacts with the test, especially if associated with D. repens infection (Fig. 2), this type of case resulting from an unknown mechanism of D. repens microfilariae, which shows a suppressive effect on those of D. immitis [38]. The ESDA does not recommend the routine heat-pretreatment of sera in area endemic for these parasitosis, as the only recommends it to resolve the discrepancy between the other tests, particularly when the dog is positive on the microfilaria test and negative by serology, and to confirm a suspicion of clinical disease suggestive of microfilaremia [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…These reactions were performed in a thermal cycler CFX96 Touch detection system (Bio-Rad, Marnes-la-Coquette, France) after activating the readers of the dyes used in each qPCR systems. After running protocol, the accumulation of the relative fluorescence units (RFUs) was recorded during the extension step of qPCRs and used to set-up the cut-off value of each TaqMan system, according to the formula described [38]. Here, we fixed the tolerance value at 5% for all systems.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dirofilariasis is recognized as a zoonosis spreading across Europe (Genchi et al, 2009;Genchi et al, 2011;Simón et al, 2012). A previous study showed that D. repens is a zoonotic parasite in Lithuania (Sabūnas et al, 2019a). In Lithuania, nine human cases of D. repens during the period of 2011-2018 and the prevalence of D. repens among shelter dogs have been reported.…”
Section: 8s-its2-28smentioning
confidence: 99%